Compressible graphene aerogel supported CoO nanostructures as a binder-free electrode for high-performance lithium-ion batteries1. Issue 12 (11th February 2015) - Dong, Yanfeng; Liu, Shaohong; Wang, Zhiyu; Liu, Yang; Zhao, Zongbin; Qiu, Jieshan
<x xml:space="preserve">Abstract</x> Binder-free electrodes have been synthesized by coupling compressible graphene aerogels with CoO nanostructures, which exhibit superior electrochemical performance to conventional electrodes made of powders and binders in lithium-ion batteries.